Determination of depths of closure along the Kelantan coast - Mohd. Ghazali, Nor Hisham (2007)
The design of beach-fill in beach nourishment works requires knowledge of the cross-shore sediment transport process. By the theory of equilibrium profiles, beachfill material will be redistributed across the shore profile up to a seaward limit known as the depth of closure or Dc. The determination of the depth of closure is a key component of beach-fill design and is measured in the field from the study of periodical surveys over the same beach profiles. The Hallermeier equation which relies on the incident pre-breaking wave height is the only analytical means to predict the depth of closure. This study has examined the applicability of the Hallermeier equation in predicting depth of closure for the coastline of Pantai Sabak, Kelantan using nearshore waves which were transformed from offshore waves through numerical modelling. The predicted depth of closure was compared against measured depth of closure at 13 profiles that were surveyed in 1998, 1999, 2000 and 2004. The widely-accepted Standard Deviation of Depth Change (SDDC) and Fixed Depth Change (FDC) methods to determine Dc were both explored and the Dc for monsoon, annual and 5-year events were investigated. The research found that along the study shoreline at Pantai Sabak, more than one closure point can occur across the same profile over the seasonal and annual period. Hallermeier’s equation overpredicts annual Dc by 43% and affirms previous findings that the predictive equation determines an upper limit value of Dc. Within the limitations of the survey data available, the annual depth of closure at Pantai Sabak can be equated to 1.5 times H0.137.